Bone marrow stromal cells induce an ALDH+ stem cell-like phenotype and enhance therapy resistance in AML through a TGF-β-p38-ALDH2 pathway - Yuan, Bin; El Dana, Fouad; Ly, Stanley; Yan, Yuanqing; Ruvolo, Vivian; Shpall, Elizabeth J.; Konopleva, Marina; Andreeff, Michael; Battula, Venkata Lokesh (PloS one, 2020)
The bone marrow microenvironment (BME) in acute myeloid leukemia (AML) consists of various cell types that support the growth of AML cells and protect them from chemotherapy. Mesenchymal stromal cells (MSCs) in the BME have been shown to contribute immensely to leukemogenesis and chemotherapy resistance in AML cells. However, the mechanism of stroma-induced chemotherapy resistance is not known. Here, we hypothesized that stromal cells promote a stem-like phenotype in AML cells, thereby inducing tumorigenecity and therapy resistance. To test our hypothesis, we co-cultured AML cell lines and patient samples with BM-derived MSCs and determined aldehyde dehydrogenase (ALDH) activity and performed gene expression profiling by RNA sequencing. We found that the percentage of ALDH + cells increased dramatically when AML cells were co-cultured with MSCs. However, among the 19 ALDH isoforms, ALDH2 and ALDH1L2 were the only two that were significantly upregulated in AML cells co-cultured with stromal cells compared to cells cultured alone. Mechanistic studies revealed that the transforming growth factor-β1 (TGF-β1)-regulated gene signature is activated in AML cells co-cultured with MSCs. Knockdown of TGF-β1 in BM-MSCs inhibited stroma-induced ALDH activity and ALDH2 expression in AML cells, whereas treatment with recombinant TGF-β1 induced the ALDH + phenotype in AML cells. We also found that TGF-β1-induced ALDH2 expression in AML cells is mediated by the non-canonical pathway through the activation of p38. Interestingly, inhibition of ALDH2 with diadzin and CVT-10216 significantly inhibited MSC-induced ALDH activity in AML cells and sensitized them to chemotherapy, even in the presence of MSCs. Collectively, BM stroma induces ALDH2 activity in AML cells through the non-canonical TGF-β pathway. Inhibition of ALDH2 sensitizes AML cells to chemotherapy.